Krishobondhu : an automated system for diagnosis of paddy disease - Rozario, Shovon Paulinus (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.